2021
DOI: 10.1126/scitranslmed.abg1143
|View full text |Cite
|
Sign up to set email alerts
|

A recombinant spike protein subunit vaccine confers protective immunity against SARS-CoV-2 infection and transmission in hamsters

Abstract: Multiple safe and effective vaccines that elicit immune responses against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) are necessary to respond to the ongoing coronavirus disease 2019 (COVID-19) pandemic. Here, we developed a protein subunit vaccine comprised of spike ectodomain protein (StriFK) plus a nitrogen bisphosphonate-modified zinc-aluminum hybrid adjuvant (FH002C). StriFK-FH002C generated substantially higher neutralizing antibody titers in mice, hamsters, and cynomolgus monkeys than t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 65 publications
1
49
0
1
Order By: Relevance
“…Hence, these other COVID-19 vaccines do not appear to induce significant mucosal protection. Modest protection was observed after immunization with a subunit spike protein vaccine with a nitrogen bisphosphonate-modified zinc-aluminum hybrid adjuvant (FH002C) where after three doses of vaccine a 50% reduction in virus transmission to naive contact animals was observed 28 . The protection against transmission we observed in our study in the SWE-adjuvated rSpike protein group was consistent with the lack of detectable infectious virus in Day 2 oropharyngeal swabs and Day 3 nasal turbinates and lungs, normally the time where peak virus replication occurs in the hamster model 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Hence, these other COVID-19 vaccines do not appear to induce significant mucosal protection. Modest protection was observed after immunization with a subunit spike protein vaccine with a nitrogen bisphosphonate-modified zinc-aluminum hybrid adjuvant (FH002C) where after three doses of vaccine a 50% reduction in virus transmission to naive contact animals was observed 28 . The protection against transmission we observed in our study in the SWE-adjuvated rSpike protein group was consistent with the lack of detectable infectious virus in Day 2 oropharyngeal swabs and Day 3 nasal turbinates and lungs, normally the time where peak virus replication occurs in the hamster model 29 .…”
Section: Discussionmentioning
confidence: 99%
“…This is relatively low, although production yields of prefusion-stabilized S vary greatly between expression systems. Yields of 0.5 mg/liter S have been reported for FreeStyle 293 cells ( 10 ), 5 mg/liter for HEK293 cells ( 56 ), and up to 200 mg/liter for stably transfected CHO cells ( 57 ). Whereas trimeric S is often unstable ( 58 , 59 ), smaller spike protein domains, for example, S1 or RBD, are generally more stable and result in higher yields.…”
Section: Discussionmentioning
confidence: 99%
“…These findings have indicated that SARS-CoV-2 mRNA vaccines can effectively promote antigen-specific Tfh cell differentiation, B cell responses and the generation of protective antibodies, which are considered as promising candidates for eliciting high-quality adaptive immune responses to control and clear SARS-CoV-2 infection. Additionally, the specific protein vaccines including SARS-CoV-2 subunit vaccine (NVX-CoV2373) with the full-length spike (S) protein, StriFK-FH002C and Spike (S)/receptor binding domain (RBD) protein subunit vaccine significantly induce specific cTfh cell and GC B cell responses, resulting in high neutralizing antibody titers of SARS-CoV-2 ( 170 172 ) ( Table 3 ). Various clinical trials in humans indicate that inactivated SARS-CoV-2 vaccines can induce satisfactory high neutralizing antibody titers that notably reduce the number of patients with severe COVID-19 ( 173 176 ).…”
Section: Tfh Cells In Sars-cov-2 Infection and Vaccinementioning
confidence: 99%